2012 IEEE/RSJ International Conference on Intelligent Robots and Systems 2012
DOI: 10.1109/iros.2012.6385632
|View full text |Cite
|
Sign up to set email alerts
|

A non-linear approach to space dimension perception by a naive agent

Abstract: Developmental Robotics offers a new approach to numerous AI features that are often taken as granted. Traditionally, perception is supposed to be an inherent capacity of the agent. Moreover, it largely relies on models built by the system's designer. A new approach is to consider perception as an experimentally acquired ability that is learned exclusively through the analysis of the agent's sensorimotor flow. Previous works, based on H.Poincaré's intuitions and the sensorimotor contingencies theory, allow a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 8 publications
1
16
0
3
Order By: Relevance
“…Philipona and co-authors showed in [44] that under certain conditions the dimensionality of space can be estimated by analyzing only sensorimotor information that is available to the agent. This result launched a series of publications by the present authors, extending the conditions of dimension estimation [45] and applying similar ideas to different agents and robotic systems [46,47,48].…”
Section: Introductionmentioning
confidence: 85%
“…Philipona and co-authors showed in [44] that under certain conditions the dimensionality of space can be estimated by analyzing only sensorimotor information that is available to the agent. This result launched a series of publications by the present authors, extending the conditions of dimension estimation [45] and applying similar ideas to different agents and robotic systems [46,47,48].…”
Section: Introductionmentioning
confidence: 85%
“…We present a neural network-based algorithm that maps a potentially high dimensional proprioception space into a low dimensional space of internal representation. The dimension of the latter is assumed known here and can be estimated using methods like in [6], [3]. We test the quality of the mapping by making a simulated robot performing reaching movements using the Jacobian of the mapping defined by the neural network.…”
Section: Introductionmentioning
confidence: 99%
“…It does not know that space is a manifold, even less that it is Euclidean. In this respect the current study is different from similar works [23], [24], [25] which made use of the implicit assumption that space has the structure of a vector space. II.…”
Section: A Spacementioning
confidence: 89%